Response of Sorghum halepense (L.) Pers. populations to nicosulfuron, rimsulfuron and cycloxidim in the Bosnia and Herzegovina - Kelečević, Biljana; Mitrić, Siniša; Simić, Maja; Dejanović, Renata (Acta herbologica, 2026)
Resistance of Sorghum halepense (L.) Pers. to acetolactate synthase (ALS) inhibitors has been reported worldwide, but has not previously been confirmed in Bosnia and Herzegovina. In this study, four populations were evaluated for their response to nicosulfuron, rimsulfuron, and cycloxydim using rhizome-derived plants. Resistance was assessed through a bioassay and molecular techniques based on PCR. Nicosulfuron and rimsulfuron were applied at 0.5×, 1×, 1.5×, and 2× the recommended dose, while cycloxydim was applied at recommended dose (1×). Phytotoxicity was assessed 20 days after treatment. Resistance to nicosulfuron and rimsulfuron was confirmed in two populations, whereas all tested populations remained susceptible to cycloxydim. Molecular analysis identified the Trp574-Leu mutation at frequencies of 14% and 50% in two populations. Given the extensive maize production and reliance on ALS inhibitors in weed control, early detection and the implementation of integrated weed management strategies are essential to delay and mitigate the spread of resistant johnsongrass.